TANGGUNG JAWAB AVIATION SECURITY DALAM PEMERIKSAAN PENUMPANG DAN BARANG DI WILAYAH BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Pradana , I Gusti Ngurah Putu Agung Wahyu (Kerta Dyatmika, 2024)
Air transportation plays a strategic role in supporting national development and integration as part of efforts to promote public welfare. One of the essential aspects in ensuring aviation security is the inspection of passengers and goods, which falls under the responsibility of Aviation Security (Avsec), as regulated by Law Number 1 of 2009 concerning Aviation. This study aims to examine the responsibilities of Aviation Security in conducting inspections of passengers and goods at I Gusti Ngurah Rai International Airport, Bali, as well as to identify the challenges faced in the execution of such duties. This research adopts an empirical legal research method, which focuses on the gap between the law in theory (das sollen) and its implementation in practice (das sein). Primary data were collected through field interviews with relevant stakeholders at the airport, while secondary data were obtained from legal documents, statutory regulations, and supporting materials. The research findings indicate that the responsibilities of Aviation Security in inspecting passengers and goods are implemented in accordance with the provisions of Law Number 1 of 2009 and the Regulation of the Director General of Civil Aviation SKEP 2765/XII/2010 concerning Procedures for Passenger Security Checks. These procedures aim to ensure a sense of safety for passengers engaging in air travel. However, the implementation of these responsibilities faces several challenges, including human resource limitations, coordination issues with law enforcement agencies, and inadequate security infrastructure and facilities. The study concludes that while the role and responsibility of Aviation Security are critical in maintaining aviation safety, efforts are still needed to enhance personnel quality, strengthen inter-agency coordination, and improve supporting infrastructure to overcome existing obstacles.